Analisis Implementasi SLiMS di Perpustakaan SMA Negeri 1 Kepanjen menggunakan model kesuksesan sistem informasi Delone Mclean - Rosy Fadilatul Ilmi (IJAL (Indonesian Journal of Academic Librarianship), 2023)
SMA Negeri 1 Kepanjen has used SLiMS as its library automation system for almost 12 years. At first the use of SLiMS was not running optimally, in 2017 it was re-optimized and finally in April 2022 SLiMS was updated to the latest version, namely SLiMS 9 Bulian. The use of SLiMS helps the collection processing process and also the circulation process to be easier, but there has never been an evaluation in the process of using SLiMS at the Library of SMA Negeri 1 Kepanjen. The importance of evaluating the use of a system in an organization is the basis for conducting this research. This research was conducted to analyze the use of SLiMS in the Library of SMA Negeri 1 Kepanjen and find out its shortcomings as evaluation material. The research was conducted using 3 variables from the Delone Mclean information system success model, namely system quality, information quality and user satisfaction with a total of 11 indicators. The research method used was a quantitative method with a total of 93 respondents. The data analysis used was descriptive analysis by calculating average and determine the mode using the help of SPSS software. Based on the analysis, it was found that the average of 3 variables used were in the high category, namely system quality (3.98), information quality (4) and user satisfaction (4.09) with data mode 4. At the end of the questionnaire, essay questions were added regarding user opinion on the use of SLiMS. The results of the answers show that the majority of users are satisfied with the use of SLiMS, but there are still some drawbacks, namely the lack of e-book collections, feature search which sometimes doesn't work properly and the difficulty of operating the system the first time you access it.